MooTools Essentials: The Official MooTools Reference for JavaScript™ and Ajax Development - Newton, Aaron (Apress, 2012)
Over the past several years, JavaScript has undergone some serious changes while simultaneously becoming more and more important to both developers and users of the Web. By now, people just expect pages to be interactive, and it’s up to you, the web developer, to meet those expectations and, when possible, exceed them. Say you went to a web site today and encountered an item—a video, a story, a photo, a download—and next to that item’s title was a five-star rating system with an invitation for you to click a star to rate it. Without thinking about it, you’d expect to be able to click the star of your choice and see the rating change. It might not surprise you if the page reloaded to ask you to register or log in, but the next time you rated something, you’d expect the rating to change to match your choice. But if every time you clicked a star the whole page reloaded, you’d feel something was wrong. Maybe you wouldn’t be able to put your finger on it (most users certainly wouldn’t think JavaScript or Ajax might be behind the problem), but something would feel odd.s